Stories for a lost child - Meland, Carter (American Indian studies series (East Lansing, Mich.), 2017)
The summer before going into high school, Fiona receives a mysterious box in the mail, one that she hopes will answer her questions about her Anishinaabe Indian heritage. It contains stories written by the grandfather she never knew, an Anishinaabe man her mother refuses to talk about. As she reads the stories, Fiona's desire to know more and her mother's reluctance to share stir up bitter feelings of anger and disappointment that slowly transform into a warmer understanding of the difficulties of family, love, and the weight of the past.